Investigating the recoveries and grades of individual platinum group and precious metals when alternative collector chemistries are used on UG2 ore. (30th March 2022) - Engelbrecht, S.; Jordaan, P.; Cloete, J.
Abstract: Iridium (Ir), platinum (Pt), palladium (Pd), rhodium (Rh) and ruthenium (Ru) are five of the six elements known as platinum group metals (PGMs). These, together with gold (Au) are classified as precious metals and make up Sibanye Stillwater's production basket. Substantial price increases for platinum (2, 4%), palladium (43, 2%) and rhodium (187, 2%) in 2020 resulted in an increase in PGM sales despite a drop in PGM production. A UG2 ore was subjected to laboratory scale flotation tests to evaluate elemental grades and recoveries of the individual elements in the production basket. As primary collector, sodium isobutyl xanthate (SIBX) was compared to a novel mass pull enhancer, a fines collector, a coarse ore collector and blends containing the novel reagents. Significant recovery improvements were seen across the whole basket. The grades of palladium and ruthenium showed room for improvement.